Upflow packed bed Anammox reactor used in two-stage deammonification of sludge digester effluent - Celen-Erdem, I; Kurt, E. S.; Bozcelik, B.; Calli, B. (IWA PUBLISHING, 2018)
The sludge digester effluent taken from a full scale municipal wastewater treatment plant (WWTP) in Istanbul, Turkey, was successfully deammonified using a laboratory scale two-stage partial nitritation (PN)/Anammox (A) process and a maximum( )nitrogen removal rate of 1.02 kg N/m(3)/d was achieved. In the PN reactor, 56.8 +/- 4% of the influent NH4-N was oxidized to NO2-N and the effluent nitrate concentration was kept below 1 mg/L with 0.5-0.7 mg/L of dissolved oxygen and pH of 7.12 +/- 12 at 24 +/- 4 degrees C. The effluent of the PN reactor was fed to an upflow packed bed Anammox reactor where high removal efficiency was achieved with NO2-N:NH4-N and NO3-N:NH4-N ratios of 1.32 +/- 0.19:1 and 0.22 +/- 0.10:1, respectively. The results show that NH4-N removal efficiency up to 98.7 +/- 2.4% and total nitrogen removal of 87.7 +/- 6.5% were achieved.
Keywords: Anammox; digester effluent; nitrogen removal rate; partial nitritation; side stream; PARTIAL NITRIFICATION; NITROGEN REMOVAL; WASTE-WATER; START-UP; BACTERIA; SCALE; Engineering; Environmental Sciences & Ecology; Water Resources